2018
DOI: 10.1016/j.radonc.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET image biomarkers improve prediction of late radiation-induced xerostomia

Abstract: Prediction of Xer was significantly improved with pre-treatment PET-IBMs, indicating that high metabolic parotid gland activity is associated with lower risk of developing late xerostomia. This study highlights the potential of incorporating patient-specific PET-derived functional characteristics into NTCP model development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…Reported data suggest that combining CT and 18 F-FDG PET features from the lung might be able to predict for radiation pneumonitis in patients receiving radiation therapy for esophageal cancer (64) or that second-order features from 18 F-FDG PET might predict radiation lung injury after SBRT for stage 1 NSCLC (65) . Similarly, high levels of parotid 18 F-FDG uptake and the texture feature of long run high gray level emphasis in patients with head and neck cancer, when added to a reference model (radiation dose and baseline xerostomia score), improved the prediction of radiation-induced xerostomia (66) .…”
Section: Radiomics and Texture Analysis In Radiation Therapymentioning
confidence: 97%
“…Reported data suggest that combining CT and 18 F-FDG PET features from the lung might be able to predict for radiation pneumonitis in patients receiving radiation therapy for esophageal cancer (64) or that second-order features from 18 F-FDG PET might predict radiation lung injury after SBRT for stage 1 NSCLC (65) . Similarly, high levels of parotid 18 F-FDG uptake and the texture feature of long run high gray level emphasis in patients with head and neck cancer, when added to a reference model (radiation dose and baseline xerostomia score), improved the prediction of radiation-induced xerostomia (66) .…”
Section: Radiomics and Texture Analysis In Radiation Therapymentioning
confidence: 97%
“…The authors concluded that the rate of CBCT-measured parotid gland image feature changes improved NTCP modeling over dose alone for late xerostomia prediction (AUC 0.77). In the context of late xerostomia prediction, baseline evaluation of changes in magnetic resonance (MR) and 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET-CT)-based parotid gland features was also shown to be a promising field of application (39)(40)(41)(42)(43). In particular, parotid glands with low metabolic activity and a low fat-to-functional parenchymal ratio were matched by more heterogeneous intensity and texture imaging features: overall, these hypothesisgenerating studies showed that pre-treatment radiomics-based prediction outperformed conventional NTCP models.…”
Section: Head and Neck Radiotherapy: Parotid Glandsmentioning
confidence: 99%
“…If using a reference constraint(s) (e.g. QUANTEC (94)(95)(96)(97)(98)(99)(100) or other extant models(3, 71,[101][102][103][104][105][106][107][108][109], note prior reference/model. (45,99,110) If constraints were based on a biological model, which one(s)?…”
Section: Processmentioning
confidence: 99%